Peran fear of failure dan fear of missing out dalam membentuk niat berwirausaha mahasiswa - Muhamad Sonhaji Sodikin; Nur Nur (Universitas Kristen Maranatha, 2025)
This study is intended to analyze the influence of fear of failure (FoF) and fear of missing out (FoMO) on entrepreneurial intention among undergraduate students in Bandung, given the intense business competition and social dynamics among young generations. The research employed a quantitative method using structural equation modeling (SEM) and involved a sample of 213 undergraduate students selected through purposive sampling. The findings indicate that fear of failure (FoF) negatively affects entrepreneurial intention, whereas fear of missing out (FoMO) enhances it. Together, these two psychological factors explain approximately 68.9% of the variance in entrepreneurial intention among students in Bandung. Therefore, entrepreneurship education programs should integrate modules on strengthening self-efficacy and resilience to mitigate fear of failure, while also leveraging fear of missing out (FoMO) as a positive motivational driver, for instance, through business mentorship and strategic planning, so that entrepreneurial intentions can be effectively realized within a well-structured long-term plan.